Evidence for the natural occurrence of Wolbachia in Aedes aegypti mosquitoes. Issue 6 (14th March 2019) - Balaji, Sivaraman; Jayachandran, Seetharaman; Prabagaran, Solai Ramatchandirane
ABSTRACT: Wolbachia, a Gram-negative bacterium, is widely known to be present in arthropods and nematodes. Of late, great impetus is given to employ this intracellular bacterium, as an alternative to conventional biocontrol agents for the control of mosquitoes because of its inherent ability to induce sperm–egg incompatibility, feminisation etc. By employing molecular tools, we have shown the presence of Wolbachia from Aedes aegypti mosquito population collected from Coimbatore, India by PCR amplifying the Ae. aegypti mosquito genome with Wolbachia specific 16S rRNA, wsp and ftsZ gene primers. The phylogenetic analysis of these gene sequences incorporating MLST and GenBank reference sequences has confirmed the occurrence of Wolbachia supergroup B in Ae. aegypti . In addition, qRT-PCR results have shown the dynamics of Wolbachia across the developmental stages of mosquito. The absence of Wolbachia in tetracycline-treated Ae. aegypti mosquitoes evidenced by transmission electron microscopy reinforced our finding conclusively. After confirming their persistence through generations, we have designated Wolbachia from Ae. aegypti as w AegB. In our considered view, w AegB could play a dynamic role in impeding mosquito multiplication and consequently impinging transmission of the dreadful dengue. Abstract : Revelation of natural Wolbachia association with the field collected Aedes aegypti mosquitoes.